Prevalence and Epidemiological Characteristics of Neuroinvasive Zoonoses in Croatia, 2017-2020. (March 2022) - Vilibic-Cavlek, T.; Stevanovic, V.; Savic, V.; Sabadi, D.; Peric, L.; Bogdanic, M.; Tabain, I.; Miklausic, B.; Santini, M.; Hunjak, B.; Potocnik-Hunjadi, T.; Dvorski, E.; et al.
Abstract : Purpose: Aseptic meningitis is one of the most common inflammatory disorders of the meninges. The etiology and epidemiology vary according to age, geographic region and immune status of the affected individuals. We analyzed the frequency and epidemiological characteristics of neuroinvasive zoonotic infections in Croatia. Methods & Materials: During a four consecutive transmission seasons (March 2017-February 2021), a total of 488 patients with clinical symptoms and laboratory findings compatible with aseptic meningitis/encephalitis were tested for the neuroinvasive zoonotic pathogens. Cerebrospinal fluid and urine samples were tested for the presence of tick-borne encephalitis (TBEV), West Nile (WNV), Usutu (USUV), Toscana (TOSV), Tahyna (TAHV), Bhanja (BHAV) and lymphocytic choriomeningitis virus (LCMV) RNA. Serum samples were tested for the presence of IgM and/or IgG antibodies to TBEV, WNV, USUV, TOSV, Borrelia burgdorferi, Anaplasma phagocytophillum and Ehrlichia chaffeensis . Patients with a history of contact with rodents were additionally tested for the presence of orthohantaviruses (Puumala; PUUV, Hantaan; HTNV, Dobrava; DOBV, Seoul; SEOV and Saaremaa; SAAV). Results: Zoonotic etiology was confirmed in 129/26.4% cases. Viral neuroinvasive infection was detected in 120/24.6% and zoonotic bacteria in 6/1.2% cases. WNV infections were most commonly reported (62/12.7%), followed by TBEV (49/10.1%). USUV infection was confirmed in 3/0.6% patients as well as TOSV. Neuroborreliosis was detected in 6/1.2% patients. In 3/0.6% patients, TBEV/ B. burgdorferi coinfection was found. Acute TAHV, BHAV, A. phagocytophilum and E. chaffeensis infections were not detected. Among rodent-borne viruses, orthohantavirus PUUV was detected in 3/0.6% patients, while LCMV was not detected during the tested period. Patients with WNV infection were older (median age 77 years) compared to other patients (median age 37-60 years). Cases showed seasonal distribution (April-November). All detected pathogens were reported in continental regions, except TOSV, which occurred at the Croatian littoral. Serologic evidence of previous infection (IgG seropositivity) showed 70/14.3% patients: B. burgdorferi 28/5.7%, A. phagocytophilum 12/2.5%, WNV 11/2.2%, TBEV 10/2.0%, TOSV 8/1.6% and USUV 1/0.2% patients. Conclusion: The presented results indicate that zoonotic viruses and bacteria are important causes of neuroinvasive infections in Croatia and should be included in the differential diagnosis of aseptic meningitis/encephalitis, especially during the transmission season (spring-autumn).